Berkhotbah Kreatif-Pastoralik dari Teks-Teks Perjanjian Lama: Pelatihan dalam Rangka Pembekalan Vikaris Gereja Toraja Mamasa Tahun 2025 - Makmur Tore'; Cantika (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2025)
Preaching is an integral part of the ministry activities of the vikaris (vicars) of the Toraja Mamasa Church (GTM). The expectations of GTM congregations toward their preachers often emphasize the preacher’s humanistic qualities. Among these expectations are the balance between the conceptual and practical aspects of preaching, the duration of the sermon, and the preacher’s style. On the one hand, such expectations reflect the congregation’s genuine need to understand the Word of God through preaching. On the other hand, preachers often view these expectations as an attitude that merely seeks to satisfy the listeners’ preferences. In this Community Service Program we carries the theme “Creative-Pastoral Preaching from Old Testament Texts.” The preaching model proposed in this program aims to bridge the tension between congregational expectations and the preacher’s concerns. The model integrates principles of adult learning, pastoral care theory, the Appreciative Inquiry research model, and homiletical theory. The material was developed using a qualitative-analytical method, in which the author conducted an in-depth analysis of the GTM context, the vicar’s context, and relevant data concerning theories related to creative-pastoral preaching. The data were collected through observation, interviews, and literature sources, which were then processed and analyzed by the author to be formulated into a journal. The outcome of this community service activity using the Pastoral Preaching Model is to enable GTM vicars to deliver the message of God’s Word in a way that is understood, received, and transformative for the congregation.